Comparison of analgesic efficacy of acetaminophen monotherapy versus acetaminophen combinations with either pethidine or parecoxib in patients undergoing laparoscopic cholecystectomy: a randomized prospective study - Francesk Mulita; Georgios Karpetas; Elias Liolis; Michail Vailas; Levan Tchabashvili; Ioannis Maroulis (Medicinski glasnik, 2020)
Aim: To investigate analgesic effect of three different regimens of combination of analgesics administered to patients undergoing laparoscopic cholecystectomy. Methods: Patients undergoing laparoscopic cholecystectomy were randomly allocated to one of three groups on admission, depending of a prescribed post-operative analgesic regimen. Patients allocated to the group A received a combination of intravenous (IV) acetaminophen and intramuscular (IM) pethidine, patients in the group B received a combination of IV acetaminophen and IV parecoxib, and the patients of the group C received IV acetaminophen monotherapy. Analgesic therapy was administered at regular intervals. Pain was evaluated utilizing the numeric rating scale (NRS) at 5 time points: the first assessment was done at 45 minutes, the second, third, fourth and fifth at 2, 6, 12, and 24 hours post-administration, respectively. Postoperative pain intensity was measured by NRS within the groups and between the groups at each time they analysed using one-way repeat measured ANOVA and Post Hoc Test-Bonferroni Correlation. Results: A total of 316 patients were enrolled. The analgesic regimens of groups A and B (combination regimens consisting of IV acetaminophen and intramuscular pethidine and IV acetaminophen and IV parecoxib, respectively) were found to be of equivalent efficacy (p=1.000). In contrast, patients in group C (acetaminophen monotherapy) had higher NRS scores, compared to both patients in groups A (p<0.01) and B (p<0.01). Conclusion: This study confirms the notion of a significant opioid-sparing effect of parecoxib in postoperative pain management after laparoscopic cholecystectomy.
Keywords: analgesia; numerical rating scale; post-operative pain